PENERAPAN METODE INVESTIGASI KELOMPOK TERHADAP PENINGKATAN KOMPETENSI MENYIMAK REKAMAN PEMENTASAN DRAMA - Nilam Sari (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This type of research is classroom action research. The research data includes observation process data and questionnaires, and result data in the form of test questions. Source of research data is 1 teacher and 35 students. The research process was analyzed using quantitative descriptive techniques. The research was conducted in two cycles each lasting three meetings. The results of the learning test for the ability to listen to recordings of drama performances through the Group Investigation method showed an increase after comparing the test results in cycle I to cycle II. The test results in cycle I only reached the sufficient category so that it affected the process and student learning outcomes. Then it was improved in cycle II by applying the Time Token Debate technique. Significant results are indicated by the proportion of cycle II test results that reach the very good category and the good category. The increase from cycle I to cycle II was 18.20.